2009
DOI: 10.1152/ajpheart.01114.2008
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of angiotensin-(1-12) in plasma and cardiac tissue in response to bilateral nephrectomy

Abstract: We examined the effects of 48 h bilateral nephrectomy on plasma and cardiac tissue expression of angiotensin-(1-12) [ANG-(1-12)], ANG I, and ANG II in adult Wistar-Kyoto rats to evaluate functional changes induced by removing renal renin. The goal was to expand the evidence of ANG-(1-12) being an alternate renin-independent, angiotensin-forming substrate. Nephrectomy yielded divergent effects on circulating and cardiac angiotensins. Significant decreases in plasma ANG-(1-12), ANG I, and ANG II levels postnephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(108 citation statements)
references
References 36 publications
9
96
3
Order By: Relevance
“…This suggests that proang-12 may be a component of only the tissue RAS in rats. To investigate the role of systemic renin in the production of proang-12, we previously measured tissue proang-12 concentrations in rats subjected to bilateral nephrectomy 17 or fed a low-salt diet. 18 Both of these experiments showed that tissue proang-12 is regulated in a manner that is independent of the plasma renin activity.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that proang-12 may be a component of only the tissue RAS in rats. To investigate the role of systemic renin in the production of proang-12, we previously measured tissue proang-12 concentrations in rats subjected to bilateral nephrectomy 17 or fed a low-salt diet. 18 Both of these experiments showed that tissue proang-12 is regulated in a manner that is independent of the plasma renin activity.…”
Section: Introductionmentioning
confidence: 99%
“…They are participating in the progression of disease, or contrary, in mechanisms that protect from tissue injury [12]. These components include the (pro) renin receptor [15,16], renin-independent mechanisms of Ang peptide generation from Ang-(1-12) [17,18], intracellular RAS [19], previously mentioned ACE2/Ang-(1-7)/Mas receptor pathway [20] and they all may possess therapeutic potential.…”
Section: Tissue and Intracellular Rasmentioning
confidence: 99%
“…(59) The unilateral nephrectomy does not cause hypertension or cardiovascular injuries. The removal of a kidney, and approximately two thirds of the other kidney leads to a slow rise in BP.…”
Section: Renopriva Hypertensionmentioning
confidence: 99%